Clicking larynx syndrome – a diagnostic and surgical challenge. Issue 6 (December 2021) - Saratziotis, Athanasios; Katsouli, Georgia; Mireas, George
Abstract: When swallowing, a clicking in the throat may uncommonly occur, causing great discomfort and pain. This unpleasant event may lead health professionals to attribute the symptoms to psychogenic aetiology. The case of a 49-year-old female is presented, who reported an audible bilateral clicking in the throat, associated with neck and throat pain when swallowing or turning her neck. From the ENT examination and palpation of the neck during patient swallowing, we located the source of the clicking on the left. However, during palpation from side to side, the patient suffered bilateral pain. Laryngeal computed tomography with a 3D reconstruction showed a short distance between the hyoid bone and the superior part of the thyroid cornua, accompanied by posterior-medially displaced bilateral superior cornua in the thyrohyoid region. The bilateral sensation of throat pain during swallowing or palpation, in combination with our desire to maintain laryngeal symmetry, led us to a two-sided exeresis of the superior thyroid cornua. This resulted in immediate and complete relief of the symptoms. Although it is an uncommon complaint, clicking larynx syndrome should be considered as a differential diagnosis.